2005
DOI: 10.1007/bf02977354
|View full text |Cite
|
Sign up to set email alerts
|

Application of microencapsulated isoflavone into milk

Abstract: This study was designed to develop a microencapsulated, water-soluble isoflavone for application into milk and to examine the hypocholesterolemic effect of such a milk product in a rat diet. The coating material was medium-chain triglyceride (MCT) and the core material was water-soluble isoflavone. The microencapsulation efficiency was 70.2% when the ratio (w/w) of coating material to core material was 15:1. The isoflavone release from the microcapsules was 8% after 3-day storage at 40 degrees C. In in vitro s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[47] In addition, similar results were investigated from the stability of microencapsulated isoflavone in gastric fluid in different incubation pHs. [48] Therefore, the present study indicated that the releasing amounts of polyphenol from peanut sprout microcapsules coated by WPC or MD in a gastric environment are minimized enough to be stable.…”
Section: Simulated Gastrointestinal Digestionmentioning
confidence: 60%
“…[47] In addition, similar results were investigated from the stability of microencapsulated isoflavone in gastric fluid in different incubation pHs. [48] Therefore, the present study indicated that the releasing amounts of polyphenol from peanut sprout microcapsules coated by WPC or MD in a gastric environment are minimized enough to be stable.…”
Section: Simulated Gastrointestinal Digestionmentioning
confidence: 60%
“…It was well correlated with a higher release of resveratrol during increasing storage time (Figure 3). Jeon et al (2005) reported that the addition of MCT as a coating material for the microencapsulated isoflavone in milk slightly but not significantly increased the color, off-flavor, bitterness, astringency and off-taste values. In overall acceptability, the lower concentration (0.5 and 1.0%) of PPSEM-supplemented milk showed a similar value to milk up to 8 d. Thus the low concentrations (0.5 and 1.0%) of PPSEM can be used as a supplement in milk without affecting the sensory properties.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, over the years, a variety of food ingredients, such as L-ascorbic acid (Lee et al, 2004), isoflavone (Jeon et al, 2005), fish oil (Fonolla et al, 2009) and Inonotus obliquus extract powder (Ahn et al, 2010) have been used in milk as microcapsules to improve the functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Functional milk has huge demand in the market with the enhanced health beneficial properties. Therefore over the years, a huge variety of food ingredients were studied, such as L-ascorbic acid (Lee et al, 2004), isoflavone (Jeon et al, 2005), and fish oil (Fomolla et al, 2009) have been used in milk to improve the functional properties.…”
Section: Introductionmentioning
confidence: 99%